Activating Neighborliness Frames: Drawing on Culturally-Relevant Discourses of Community to Build a Stronger and More Diverse Environmental Movement - Carlisle, Liz (Frontiers in Communication, 2020)
In this article, I draw on my experience as an environmental social scientist and narrative nonfiction writer working in working class conservative communities that frequently challenge or reject science communication. Based on my own trial-and-error path as a public intellectual working to advance sustainable agriculture, I present a method that I’ve developed to promote broader and more diverse public dialogue about environmental problem solving. Acknowledging that people interpret the world through socially-reinforced cultural cognition and pre-existing cognitive frames — and also that humans are social animals who thrive in groups — I propose that frames can be the science communicator’s friend. I have yet to find a community that does not have some connection to ancestral or local knowledge about community interdependence and the importance of being a good neighbor. Indeed, I often find that these “neighborliness” frames are at the very core of people’s cultural cognition. Such neighborliness frames, in turn, provide a strong foundation for environmental consciousness. Thus, by being curious about a community’s unique history with and knowledge about neighborliness, science communicators can help to build up frames necessary for environmental actions, while also helping cultivate broader understandings of the “neighborhood” within which communities’ values and worldviews demand action.